(untitled) (Proceedings of International Conference on Special Education, 2015)
Being able to be independent and employed after leaving school is every parent’s dreams of their special needs children. To assist these special needs children to function in work environment, a transition program was designed individually for the students’ specific abilities. This transition program from school to work is aimed to train special needs children the skills that are needed for them to work in a specific work environment. This program assists the special needs students to acquire certain skills and gain work experiences in the real workplace. This case study focused on a 16 year-old male student with learning disabilities who was selected were designed to train the students the skills needed in his future work environment. This study found that the student was able to acquire the work skills taught and was placed in the work after he finished the training at school. The findings also indicated that the student had faced several challenges at the beginning of the internship such as adapting to the new surrounding and communicating with co-workers and supervisor. But at the end of the transition program he successfully completed the internship and overcome his social and behavior issues. The program also raised his self-confidence that he is looking forward to work and earns a living in the future.